2017
DOI: 10.1007/s10530-017-1594-y
|View full text |Cite
|
Sign up to set email alerts
|

Naturalization of ornamental plant species in public green spaces and private gardens

Abstract: Ornamental horticulture is the most important pathway for alien plant introductions worldwide, and consequently, invasive spread of introduced plants often begins in urban areas. Although most introduced ornamental garden-plant species are locally not naturalized yet, many of them have shown invasion potential elsewhere in the world, and might naturalize when climate changes. We inventoried the planted flora of 50 public and 61 private gardens in Radolfzell, a small city in southern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 50 publications
(48 reference statements)
5
47
0
1
Order By: Relevance
“…The ones that did test it also demonstrated its importance (Feng et al., ; Mayer et al., ). The significance of propagule pressure for plant invasions is well‐established (Bucharová & van Kleunen, ; Dehnen‐Schmutz, Touza, Perrings, & Williamson, ; Feng et al., ; Hanspach et al., ; Lockwood et al., ; Pyšek et al., ), and the same is true for the effect of naturalisation or invasion success elsewhere (Klonner, Fischer, Essl, & Dullinger, ; Kolar & Lodge, ; Mayer et al., ; Reichard & Hamilton, ). Compared to those other studies, which included naturalisation elsewhere primarily as a binary metric (yes, no), our study shows that more detailed information on the number of regions where a species is naturalised further improves the predictive value of naturalisation elsewhere (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ones that did test it also demonstrated its importance (Feng et al., ; Mayer et al., ). The significance of propagule pressure for plant invasions is well‐established (Bucharová & van Kleunen, ; Dehnen‐Schmutz, Touza, Perrings, & Williamson, ; Feng et al., ; Hanspach et al., ; Lockwood et al., ; Pyšek et al., ), and the same is true for the effect of naturalisation or invasion success elsewhere (Klonner, Fischer, Essl, & Dullinger, ; Kolar & Lodge, ; Mayer et al., ; Reichard & Hamilton, ). Compared to those other studies, which included naturalisation elsewhere primarily as a binary metric (yes, no), our study shows that more detailed information on the number of regions where a species is naturalised further improves the predictive value of naturalisation elsewhere (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While the importance of climatic suitability is widely acknowledged, few studies have tested it explicitly. The ones that did test it also demonstrated its importance (Feng et al, 2016;Mayer et al, 2017). The significance of propagule pressure for plant invasions is well-established (Bucharová & van Kleunen, 2009;Dehnen-Schmutz, Touza, Perrings, & Williamson, 2007b;Feng et al, 2016;Hanspach et al, 2008;Lockwood et al, 2005;Pyšek et al, 2009b), and the same is true for the effect of naturalisation or invasion success elsewhere (Klonner, Fischer, Essl, & Dullinger, 2016;Kolar & Lodge, 2001;Mayer et al, 2017;Reichard & Hamilton, 1997).…”
Section: Predictors Of Naturalisation Successmentioning
confidence: 95%
See 1 more Smart Citation
“…McLean et al (2017) show, for small urban centres in South Africa, that many non-native plant species enter towns via the horticultural ornamental trade and that half of the most abundant non-native species in towns have established naturalized populations outside urban areas. Similarly, Mayer et al (2017) found that a considerable number of ornamental plants were naturalized in Radolfzell, Germany.…”
Section: Managing Biological Invasions In Urban Areasmentioning
confidence: 92%
“…Proactive management at an early stage of invasion is required to minimize public costs. Mayer et al (2017) determine factors that lead to horticultural plants naturalizing and provide a framework to determine future threats. emphasize the need to focus action on urban green areas as launching sites for invasions and provide a system for ranking cities.…”
Section: Are Patterns and Processes Of Urban Invasions Different Frommentioning
confidence: 99%